What Is African American Literature? - Crawford, Margo N (Wiley Blackwell Manifestos, 2021)
After Kenneth W. Warren's What Was African American Literature?, Margo N. Crawford delivers What is African American Literature? The idea of African American literature may be much more than literature written by authors who identify as "Black". What is African American Literature? focuses on feeling as form in order to show that African American literature is an archive of feelings, a tradition of the tension between uncontainable black affect and rigid historical structure. Margo N. Crawford argues that textual production of affect (such as blush, vibration, shiver, twitch, and wink) reveals that African American literature keeps reimagining a black collective nervous system. Crawford foregrounds the "idea" of African American literature and uncovers the "black feeling world" co-created by writers and readers. Rejecting the notion that there are no formal lines separating African American literature and a broader American literary tradition, Crawford contends that the distinguishing feature of African American literature is a "moodscape" that is as stable as electricity. Presenting a fresh perspective on the affective atmosphere of African American literature, this compelling text frames central questions around the "idea" of African American literature, shows the limits of historicism in explaining the mood of African American literature and addresses textual production in the creation of the African American literary tradition. Part of the acclaimed Wiley Blackwell Manifestos series, What is African American Literature? is a significant addition to scholarship in the field. Professors and students of American literature, African American literature, and Black Studies will find this book an invaluable source of fresh perspectives and new insights on America's black literary tradition.